2023
DOI: 10.3389/fcimb.2023.1223824
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and mortality risk factors of mixed bacterial infections in hematopoietic stem cell transplantation recipients

Yanfeng Liu,
Yi Liu,
Xuefeng Chen
et al.

Abstract: Background and objectiveMixed bacterial infections (MBI) is one of the complications after hematopoietic stem cell transplantation (HSCT) and increases the risk of patient death. However, there are few reports specifically on this topic. The purpose of this study was to investigate the clinical characteristics and mortality risk factors of MBI in HSCT recipients.MethodsThe electronic medical records of patients undergoing HSCT were collected. The epidemiological features and antibiotic resistance of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
1
0
0
Order By: Relevance
“…Patients with a history of perianal infection have a higher probability of reinfection than those without perianal infection, regardless of treatment success. 22 Mo et al 23 found that a history of perianal infection was an independent risk factor for perianal infection, which was consistent with the results of this study. In this study, 27.14% (34/124) of the patients with perianal infection had a history of perianal infection.…”
Section: Open Accesssupporting
confidence: 92%
“…Patients with a history of perianal infection have a higher probability of reinfection than those without perianal infection, regardless of treatment success. 22 Mo et al 23 found that a history of perianal infection was an independent risk factor for perianal infection, which was consistent with the results of this study. In this study, 27.14% (34/124) of the patients with perianal infection had a history of perianal infection.…”
Section: Open Accesssupporting
confidence: 92%